Failure to report of chest pain - Navvabi, S (Iran University of Medical Sciences, 1995)
55 patients, who admitted during three month to CCU ward of one academic hospital, participated in this study. 80% of these patients had delay to report of their chest pain and 4% of them had complete failure to report it. Reasons for didn't report of pain and its signs were unawareness of nurse and physician about problem that is occurring and unawareness of patient about need to saying this problem and finally was difficulty in nurse-patient communication.  Why patients don't report onset of chest pain in CCU ward? Researchers showed that many of these patients experienced pneumonia and ... in their childhood. Appropriate and enough use of analgesic drugs in CCU is very important because high level of anxiety due to chest pain cause to increase catecholamines' secretion and also increase consumption of reserved oxygen of myocardium. Increased chest pain was occurred as a result of myocardial ischemia and probably arrhythmia was happened.  Patients who had severe and prolonged pain need to more use of analgesic. These patients may be faced with extensive ischemia and even recurrence of myocardial infarction. On the other hand, patients with prolonged pain had lower mortality than patients who had not pain. There are many problems related to pain in CCU ward because nature of disease was determined by chest pain. This type of pain was ranged from inconvenience feeling to compression state. Pain radiated to arms, back, jaw, neck and shoulder. One study was performed in America and 19 patients who admitted to CCU ward participated in this study. 80% of women, namely from each five women, four cases and 71.4% of men namely, from each 14 men, 10 cases didn't report their chest pain. Four reasons were found about this failure to report: 1- Pain was not enough severe. 2- Patient didn't want annoys ward's personals with his/her complaint. 3- Patient tries to find method of pain relief. 4- he/she has had error, confusion and misconception about diagnosis of pain